Capacidade funcional de idosos inseridos em um programa de fisioterapia na atenção primária à saúde - Santos, Paula Correa Neto (2022)
The assessment of the functional capacity (FC) of the elderly has been increasingly used in research and clinical practice due to its predictive value for events that influence healthy aging. Aging is a heterogeneous and dynamic process, associated with biological, psychological, lifestyle, socioeconomic and environmental characteristics. These elements ratify the need for the elaboration and (re)organization of strategies aimed at the care of this population, with the aim of maintaining FC for as long as possible, to improve the quality of life and minimize family dependence. The physical functionality of the elderly can be evaluated according to their mobility condition and ability to perform activities of daily living (ADL's). It is a challenge to care for the elderly, considering the complexity of health issues and comprehensive care actions from a functional perspective. This research stands out for its originality and the scarcity of studies that simultaneously use two instruments to assess the FC of the elderly in primary health care (PHC) in Brazil. This Master's degree dissertation was built in the form of a scientific article and aimed to evaluate the effects of a physical therapy program on the FC of the elderly. A quasi-experimental before and after study was develop, with data collected retrospectively from medical records between august and December 2019. The sample consisted of 97 elderly people who participated in a PHC program provided by the physiotherapy service of the University Clinical Health Center, in a municipality in the south of Goiás. Three assessment instruments were used, a structured questionnaire to characterize the sample, with information on health conditions and sociodemographic variables; the Independence in Activities of Daily Living Scale (IADLS) or Katz Scale, to assess performance in ADL's; and the Short Physical Performance Balance (SPPB), which evaluated CP advocating lower limb strength (LL), static balance and gait. The comparison of EIAVD and SPPB scores before and after the intervention was performed using the Wilcoxon test; and the z statistic (coefficient of statistical power) was used to compare the intervention according to the exploratory variables of the group (age group, schooling, sex, marital status, family income, time and weekly frequency in the program). The comparison of the IADLS and SPPB classification before and after the intervention was performed using the Chi-square test, followed by Posthoc. The significance level adopted was 5% (p < 0, 05). Most of the elderly were female, married and had elementary education, lived mainly with their spouses, two people contributed to the family income and received up to three minimum wages. After the physiotherapy program, the elderly improved in the items bathing (p=0,014), dressing (p=0,046), transference (p=0,025) and in the total score (p=0,001). As for the SPPB, there was an improvement in all tests and in the total score; decrease in the number of patients with poor performance and increase in the number of patients with good performance (p<0,001). When comparing the evolution of the IADLS according to the profile variables, there was an improvement in the elderly aged between 60 and 70 years (p=0,014); female (p=0,002); with a partner (p=0,014) and without a partner (p=0,023); both illiterate elderly (p=0,046) and those with elementary education (p=0,023); with a family income of 1 to 2 (p=0,010) and 3 to 6 minimum wages (p=0,025); with time in the program between 6 to 10 months (p=0,002); and with a weekly frequency of 2 (p=0,008) and 3 times in the program (p=0,038). As for the SPPB, there was an improvement according to all the analyzed variables (p<0,001). It is concluded that elderly participants of physical activity programs in primary care showed an improvement in their PC and progress in their basic activities of daily living